Strategi Petani Desa Segayam Dalam Menghadapi Tantangan Pertanian Modern - Stevy Arta Meilia; Dion Bernolian; Rinni Dwi Andayani; Cindy Cintya; Nugroho Agung Saputra; Agra Dwi saputra (CV. ITTC INDONESIA, 2026)
This study aims to analyze the strategies of farmers in Segayam Village in facing the challenges of modern agriculture characterized by climate change, fluctuating commodity prices, increasing production costs, and developments in agricultural technology. The study employed a qualitative approach with descriptive methods. Data were collected through in-depth interviews, field observations, and documentation. Data were then analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that farmers employ various adaptive strategies, including gradual technology adoption, crop diversification to reduce risk, institutional strengthening through farmer groups, production cost efficiency, and expanding market access through distribution networks and digital media. These strategies reflect farmers' adaptive capacity in responding dynamically to social, economic, and environmental pressures to maintain the stability and sustainability of their farming businesses. However, challenges such as limited capital and unstable market access remain obstacles to optimizing agricultural output. This study concludes that farmers' adaptive capacity is a key factor in maintaining the sustainability of rural agriculture amidst the dynamics of agricultural sector modernization.